Combining photothermal ablation-based vaccine with immune checkpoint blockade for synergistic osteosarcoma immunotherapy - Xingyu Zhao; Yu Han; Yang Sun; Wei Feng; Jianguo Liu; Dongsong Li; Tiejun Wang (Materials & Design, 2021)
Osteosarcoma is a serious bone malignancy that threatens to human health, while the conventional chemotherapy exhibits ineffective and severe side effects. Here, a multi-approach for primary and metastatic tumors was developed by combining photothermal ablation-based in situ tumor vaccine with PD-1/PD-L1 blockade immunotherapy. Polyethyleimine modified golden nanorod (GNR-PEI) was prepared by conjugating of hyperbranched PEI to GNR via SAu bonds. The positive charged GNR-PEI could complex with cyclic dimeric guanosine monophosphate-adenosine monophosphate (cGAMP) by electrostatic interaction. GNR-PEI/cGAMP complex was further utilized for near-infrared laser-triggered phototherapy of primary tumors, generating in situ tumor vaccine, recruiting dendritic cells (DCs) to capture tumor-associated antigens. In addition, cGAMP is a kind of stimulator of interferon genes (STING) agonist that can stimulate the expansion and activation of DCs, arousing the specific immune killing effect of cytotoxic T cells. Furthermore, the combination of localized tumor vaccine and programmed cell death protein-1 (PD-1) monoclonal antibody (anti-PD-1), that could achieve the checkpoint-blockade and reverse tumor immune tolerance microenvironment, thus improving T cells specific recognition and killing of remaining and metastasis tumor cells. Hence, this combined strategy is expected to be further used in the clinical treatment of osteosarcoma.